التنخطيط الإستراتيجي وأثره على تحسين الأداء في ضوء جودة القرارات "دراسة ميدانية على الإدارة الريسية لجامعة الجبل الغربي في دولة ليبيا والكليات التابعة لها - 'Abdul Salam Muhammad 'Asyur Bilqasim
This study aims at identifying the constructive sincerity of the learning criteria, analysing and evaluating the relationship between the strategic planning, the strategic performance level and the strategic decisions quality at Al Jabal Al Gharbi University, as well as assessing the role of its quality decisions in enhancing the indirect relation between the strategic planning and the level of the strategic performance. The researcher adopted the descriptive qualitative and quantitative statistic methods besides the scientific observation, personal interview and the questionnaire as tools to collect and analyse data via a sample contains 378 individuals of all the leaders and officials of Al Jabal Al Gharbi University through SPSS program and the modelling of structural formula style (SEM-AMOS). The study concludes: - the existence of factors and confirmative structure behind the learning criteria characterised by the constructive sincerity, The strong obligatory relationship between the strategic planning and the level of the strategic performance within the existence of the strategic decisions quality. This study contributes, in the context of theory, at building and shaping a developed scientific model that clarifies the relations among its main variables and elements. Also it contributes, in the context of practical, to be applied on Al Jabal Al Gharbi University using three developed statistic methods to prove that the university success in performance does not depends only on the strategic planning, but on the quality of its decisions as well.